Coinfection with Hepatitis C and HIV Is a Risk Factor for Poor Outcomes After Total Knee Arthroplasty. Issue 3 (28th September 2017) - Mahure, Siddharth A.; Bosco, Joseph A.; Slover, James D.; Vigdorchik, Jonathan M.; Iorio, Richard; Schwarzkopf, Ran
Abstract : Background: As medical management continues to improve, orthopaedic surgeons are likely to encounter a greater proportion of patients who have coinfection with human immunodeficiency virus (HIV) and hepatitis-C virus (HCV). Methods: The New York Statewide Planning and Research Cooperative System (SPARCS) database was used to identify patients undergoing total knee arthroplasty between 2010 and 2014. Patients were stratified into 4 groups on the basis of HCV and HIV status. Differences regarding baseline demographics, length of stay, total charges, discharge disposition, in-hospital complications and mortality, and 90-day hospital readmission were calculated. Results: Between 2010 and 2014, a total of 137, 801 patients underwent total knee arthroplasty. Of those, 99.13% (136, 604) of the population were not infected, 0.62% (851) had HCV monoinfection, 0.20% (278) had HIV monoinfection, and 0.05% (68) were coinfected with both HCV and HIV. Coinfected patients were more likely to be younger, female, a member of a minority group, homeless, and insured by Medicare or Medicaid, and to have a history of substance abuse. HCV and HIV coinfection was a significant independent risk factor for increased length of hospital stay (odds ratio [OR], 2.9; 95% confidence interval [CI], 1.75 to 4.81), total hospital charges in the 90th percentile (OR, 2.02; 95% CI, 1.12 to 3.67), ≥2 in-hospital complications (OR, 2.04; 95% CI, 1.04 to 3.97), and 90-day hospital readmission (OR, 3.53; 95% CI, 2.02 to 6.18). Conclusions: Patients coinfected with both HCV and HIV represent a rare but increasing population of individuals undergoing total knee arthroplasty. Recognition of unique baseline demographics in these patients that may lead to suboptimal outcomes will allow appropriate preoperative management and multidisciplinary coordination to reduce morbidity and mortality while containing costs. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.